Kipling and "Orientalism"'s: Cracks in the Wall of Imperial Narrative. Issue 1 (2nd January 2018) - Morey, Peter
Abstract : This essay takes inspiration from Bart Moore-Gilbert's career-long fascination with the work of Rudyard Kipling. It explores features of Kipling's short stories, such as ideological ellipses and unreliable narration, to reveal how British imperialism's grasp on power-knowledge was always slippery and uncertain. While Kipling's stories emphasize the sacrifice of the imperial servant – exhibiting what Moore-Gilbert calls an "Anglo-Indian Orientalism" based on the better knowledge of those actually serving the Raj, to set against the glamourizing tendencies of "Metropolitan Orientalism" – they nonetheless often point to a lack of knowledge in the narrator as he seeks to procure narratives that will be useful to the British. In particular, the compromised position of the narrator in the story "On the City Wall" – with his desperate attempts to police information – illustrates that controlling the flow of power-knowledge exposes the collision between surveillance and violence that always lies behind imperial forms of governance.